Non-puerperal uterine inversion with submucous fibroid - A rare case report - -, Shambhavi; -, Priyanka (Indian Journal of Case Reports, 2018)
Uterine inversion is an unusual, rare entity in which the uterus descends in reverse direction exposing endometrial surface throughthe cervix and classified as puerperal or obstetric and non-puerperal or gynecological inversion. Non-puerperal uterine inversionis very rare and often clinically misdiagnosed by the clinician. Cervix remains drawn up thus making the vaginal part of cervixdifficult to palpate. Acute inversion usually occurs in the 3rd stage of the labor and is an obstetric emergency. Diagnosis is based onthe clinical and imaging techniques. We report a case of a postmenopausal non-puerperal uterine inversion secondary to submucousfibroid and its successful management.